Concentrations and biomagnification of multiple metals/metalloids are higher in rice than in sugarcane agroecosystems of southern China - Wambura M. Mtemi; Shilong Liu; Kangmei Liu; Lini Wei; Xueli Wang; Aiwu Jiang; Eben Goodale (Ecological Indicators, 2023)
Agricultural lands have been increasingly reported to be contaminated by metals and metalloids, leading to exposure to these toxins for humans and wildlife. Previous studies on metal/metalloid contamination have reported biomagnification of total elemental Hg (THg) and, less consistently, of Cd, in both aquatic and terrestrial ecosystems. Whether other metals or metalloids can biomagnify in food webs, especially those that produce food for humans, is uncertain. We aimed to compare metal/metalloid contamination and their biomagnification patterns between rice paddy and sugarcane agroecosystems. We collected samples at an inactive Pb-Zn mine site, and two reference sites in southwestern Guangxi, southern China. Samples were widely distributed across the food web, including soil, rice grain and leaves, sugarcane leaves, crickets, grasshoppers, spiders, and frogs. We found that Cr, Cd, Pb, THg, and Zn were the metals associated with mining activities, while As and Cu were higher at the reference sites. In soil, and in the majority of species for which there were significant differences between agroecosystems, concentrations of Cd, Cr, Cu, Pb, THg, and Zn were higher in rice, suggesting that the rice paddy ecosystem is particularly sensitive to metal contamination. When quantitatively rating the patterns of biomagnification using post-hoc multiple comparisons among species’ bioaccumulation factors (BAFs), rice paddies had stronger patterns of biomagnification (3 strong relationships [e.g., all insectivores had higher or as high BAFs compared to all other species], 7 medium relationships [e.g., one of the insectivores had the highest BAFs, but another had an intermediary value, similar to an herbivore], 6 weak [e.g., one insectivore had the highest BAFs, but the other was as low as a primary producer], and 3 no relationships [e.g., no significant differences among species in BAFs]) than sugarcane ecosystems (1 strong, 2 medium, 8 weak, and 9 no relationships; Repeated measures t-test, P-value = 0.0023) across 6 metals (Cr, Cd, Cu, Hg, Pb, Zn). The strongest biomagnification was evident for THg and Zn, whereas an intermediary level of biomagnification was found for Cd, Cr, Cu, and Pb; biodilution was observed for As and Mn. Therefore, focusing on metal/metalloid apportionment to better understand the sources of the metals at our study sites would be of utility to lower the exposure of wildlife and people. Most importantly, the local authorities should check metal concentrations in any farming product from the mining area and even the close reference site to safeguard human health.